The effect of social context and learning on aggression biases: consequences for the role of male-male competition in speciation and a field study in cichlid fish - Dijkstra, Peter D.; Seehausen, Ole (Frontiers in Ecology and Evolution, 2025)
Male-male competition and female-female competition can play important roles in the origin and maintenance of phenotypic polymorphism and speciation. If territory owners bias aggression towards others of their own phenotype, rare male phenotypes will be involved in fewer costly fights, facilitating the evolution of diversity, and stabilizing the coexistence of distinct phenotypes or species. However, the mechanisms that regulate aggression biases have received little attention. We discuss how learning and plasticity in behavioral biases may dramatically influence how aggression biases evolve, which in turn may have important consequences for clarifying the role of intrasexual competition in the process of speciation. We then present data from a field study of two cichlid species in Lake Victoria and illustrate how the social environment could modulate aggression biases of territorial males towards specific intruder phenotypes. Specifically, in Pundamilia nyererei (males are red) and P. ‘pink anal’ (males are blue), blue territory holders showed a tendency to shift their aggression bias more towards red intruder (stimulus) males relative to blue intruder males when these territory holders had more red territorial neighbors. By contrast, red territory holders tended to reduce aggression towards red intruder males relative to blue intruder males when they were surrounded by more red territorial neighbors. Although sample sizes are small, our data suggest that social context may shape aggression biases in the Pundamilia species complex and that these effects may vary between species. We conclude that considering the social environment and experience in shaping aggression biases may advance our understanding of how mate competition shapes evolutionary patterns of phenotypic diversification.